Growth and characterization of metamorphic layer structures for high electron mobility transistors - Yuan, Kaihua. (2008)
InP-based high electron mobility transistors (HEMTs) have demonstrated superior high frequency and low noise performance. However, high cost, limited size and brittle nature of InP substrate bring difficulties to low-cost and high-volume production. In order to overcome these drawbacks, it is desirable to develop InP-based metamorphic HEMT devices on GaAs substrates. In this case, the compositionally graded metamorphic buffer layers are widely used to accommodate the large lattice mismatch between the GaAs substrate and the top active layers.